2020
DOI: 10.1101/2020.12.01.405514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Host-pathogen genetic interactions underlie tuberculosis susceptibility

Abstract: The outcome of an encounter with Mycobacterium tuberculosis (Mtb) depends on interactions between the heterogeneous immune response of the host and the ability of the pathogen to adapt. Understanding this interplay has proven difficult, largely because experimentally tractable small animal models do not recapitulate the heterogenous disease observed in natural infections. We leveraged the genetically diverse Collaborative Cross (CC) mouse panel in conjunction with a library of Mtb mutants to associate bacteria… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…We examined the predicted operon of one other cAMP-binding protein, the transcription factor CRP MT , and found that only a handful of these genes were differentially expressed in a cAMP-dependent and/or Rv1625c-dependent manner during growth in cholesterol media (Fig 8). Notably, three of these genes are required for optimal growth of Mtb in cholesterol media and/or in mouse models of TB, but are not directly involved in cholesterol side chain or ring breakdown [12,45]. Most of the remaining genes do not have established functions, making it difficult to predict how changes in their expression could impact specific aspects of Mtb physiology.…”
Section: Plos Pathogensmentioning
confidence: 99%
See 1 more Smart Citation
“…We examined the predicted operon of one other cAMP-binding protein, the transcription factor CRP MT , and found that only a handful of these genes were differentially expressed in a cAMP-dependent and/or Rv1625c-dependent manner during growth in cholesterol media (Fig 8). Notably, three of these genes are required for optimal growth of Mtb in cholesterol media and/or in mouse models of TB, but are not directly involved in cholesterol side chain or ring breakdown [12,45]. Most of the remaining genes do not have established functions, making it difficult to predict how changes in their expression could impact specific aspects of Mtb physiology.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…Mtb completely degrades cholesterol into two-and three-carbon intermediates that are metabolized for energy production or serve as biosynthetic precursors of cell wall or virulence lipids [6]. In animal models, Mtb requires cholesterol metabolism to maintain optimal chronic lung infection [7][8][9][10][11] and cholesterol utilization was recently found to belong to a set of "core virulence functions" required for Mtb survival in vivo across a genetically diverse panel of mice [12]. Furthermore, it was recently demonstrated that a multi-drug resistant strain of Mtb is more dependent on cholesterol for growth than the H37Rv reference strain [13].…”
Section: Introductionmentioning
confidence: 99%
“…To place the variability in genetic requirements we observed between bacterial isolates from different phylogenetic lineages into broader biological context, we considered a recently published TnSeq study which investigated Mtb requirements for infection across genetically and immunologically diverse mouse backgrounds 63 . In this study, an H37Rv transposon library was used to infect a panel of 60 mouse genotypes encompassing strains from the Collaborative Cross collection and mice with specific immunological deficits, such as IFNγ knockout.…”
Section: Functional Genomic Analysis Of Mtb Strains During Infectionmentioning
confidence: 99%
“…A non-redundant role for RodA in protection against cell wall damage. The contribution of RodAMtb to M. tuberculosis survival in different in vivo models (29,(35)(36)(37)39) and the requirement for RodAMsm in the damage-induced sidewall shift in M. smegmatis peptidoglycan synthesis (Fig. 4) suggested that the enzyme could play a non-redundant role in protecting against cell wall stress.…”
Section: Roda But Not Apbps Contributes To Redistribution Of Peptidoglycan Synthesismentioning
confidence: 99%
“…Why have these organisms retained enzymatically-redundant systems for peptidoglycan synthesis? One clue may arise from work with the human pathogen M. tuberculosis, where RodA and the aPBPs individually contribute to survival in immune cells, some mouse backgrounds, and in a guinea pig model (29,(35)(36)(37)(38)(39). These observations suggest that RodA and the aPBPs play unique roles in protecting mycobacteria from stress.…”
Section: Introductionmentioning
confidence: 99%